A Cloud-Based Crime Reporting System with Identity Protection - Tzay-Farn Shih (Symmetry, 2019)
Criminal activities have always been a part of human society, and even today, in a world of extremely advanced surveillance and policing capabilities, many different kinds of crimes are still committed in almost every social environment. However, since those who commit crimes are not representative of the majority of their community, members of these communities tend to wish to report crime when they see it; however, they are often reluctant to do so for fear of their own safety should the people they report identify them. Thus, a great deal of crime goes unreported, and investigations fail to gain key evidence from witnesses, which serves only to foster an environment in which criminal activity is more likely to occur. In order to address this problem, this paper proposes an online illegal event reporting scheme based on cloud technology, which combines digital certificates, symmetric keys, asymmetric keys, and digital signatures. The proposed scheme can process illegal activity reports from the reporting event to the issuing of a reward. The scheme not only ensures informers’ safety, anonymity and non-repudiation, but also prevents cases and reports being erased, and ensures data integrity. Furthermore, the proposed scheme is designed to be robust against abusive use, and is able to preclude false reports. Therefore, it provides a convenient and secure platform for reporting and fighting crime.